THERAPEUTIC POTENTIAL OF HERBAL REMEDIES USED IN MANAGEMENT OF REFLUX ESOPHAGITIS (CAHIERS MAGELLANES-NS, 2024)
Reflux esophagitis is most common disease which is affecting population globally lowering the quality of life. When it comes to treating this disease there are multiple factors responsible for causation hence it requires longer time for relief of symptoms. Evaluation of these causes is very essential commonest causes are food –diet-sleep pattern, mental stress, obesity, genetic history and many more. Hence it is seen that management becomes difficult hence patient might shift from one treatment modality to another to get relief which has negative effects which need to be overcome. There are numerous plants and herbs which are commonly used as home remedies for this disorder. They are usually beneficial in relieving symptoms. The current review focuses on plants having medicinal value and clinically demonstrated to have efficacy in management   of reflux esophagitis